If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.5x + 6y = 8 Solving -1.5x + 6y = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. -1.5x + 6y + -6y = 8 + -6y Combine like terms: 6y + -6y = 0 -1.5x + 0 = 8 + -6y -1.5x = 8 + -6y Divide each side by '-1.5'. x = -5.333333333 + 4y Simplifying x = -5.333333333 + 4y
| 5X-2(X+3)-1=9(2X-5) | | 9x-9=6x+6 | | -2x-29=-7(3x-4) | | x^2-10x+90=9 | | -27*-32= | | 19x-13=-103 | | 5x^3+10=40 | | 47*-16= | | 186x-y=10 | | x^3+7=-1 | | 7x^2-x-12= | | x^2-6x=8x+80 | | -14*92= | | 4x+4y+5z= | | -8(n+4)=-14-5n | | 0.50x+30=55 | | x^3+8=133 | | -16*92= | | y=2x+90 | | 3x^3=63 | | 2(m+29)-12=80 | | 7x-27+4x+12=180 | | x^2-x-66=6 | | 5x^3=125 | | x^4+x^2-2x-1=0 | | 42x^2+67x+21= | | 4y+ax=b+8y(x) | | x^3-x-2= | | -11*-24= | | -9x+9y=27 | | 15n+18=-6n+2 | | 2-2n=3(-n+2) |